The Effects of a Digital Game Simulator versus a Traditional Intervention on Paramedics' Neonatal Resuscitation Performance - Maria Cutumisu; Georg M. Schmölzer (MDPI AG, 2024)
Neonatal resuscitation is a skill set that comprises procedures, assessment, decision-making, communication, and teamwork. It is used in an emergency situation in the delivery room with the aim of supporting newborn infants who are not able to begin breathing on their own. Thus, healthcare providers need to refresh their neonatal resuscitation skills periodically, according to the Neonatal Resuscitation Program, to ensure that they can react quickly and effectively in emergency situations. The RETAIN digital game simulator was designed to enable healthcare providers to practice their neonatal resuscitation skills. To evaluate the effectiveness of this game in a laboratory setting, a randomized control trial sampled 42 paramedics who completed a pre-test, were randomly assigned to watch a traditional lecture video on the neonatal resuscitation procedure or to play a novel digital game simulation on the same topic, and then completed a following test. A two-way mixed ANOVA revealed a statistically significant improvement in paramedics' neonatal resuscitation performance over time, which did not differ between conditions. Thus, digital games can provide an enjoyable alternative to traditional practices in refreshing neonatal resuscitation knowledge.